Sensors and microsystems proceedings of the AISEM 2020 Regional Workshop. - Di Francia, Girolamo; Di Natale, Corrado (Lecture Notes in Electrical Engineering, 2021)
This book showcases the state of the art in the field of sensors and microsystems, revealing the impressive potential of novel methodologies and technologies. It covers a broad range of aspects, including: bio-, physical and chemical sensors, actuators, micro- and nano-structured materials, mechanisms of interaction and signal transduction, polymers and biomaterials, sensor electronics and instrumentation, analytical microsystems, recognition systems and signal analysis and sensor networks as well as manufacturing technologies, environmental, food, energy and biomedical applications. The book gathers a selection of papers presented at the AISEM Regional Workshop on Sensors and Microsystems, held in Portici (Naples), Italy in February 2020.